An Ultra‐Broadband High Efficiency Polarization Beam Splitter for High Spectral Resolution Polarimetric Imaging in the Near Infrared. Issue 27 (12th July 2022) - Hsiao, Hui‐Hsin; Muller, Richard E.; McGuire, James P.; Nemchick, Deacon J.; Shen, Chin‐Hung; Harten, Gerard van; Rud, Mayer; Johnson, William R.; Nordman, Austin D.; Wu, Yen‐Hung; Wilson, Daniel W.; Chiou, Yih‐Peng; et al.
Abstract: A broadband, high efficiency polarized beam splitter (PBS) metagrating based on integrated resonant units (IRUs) to enable simultaneous polarization analysis, spectral dispersion, and spatial imaging in the near infrared (NIR) is developed. A PBS metagrating with a diameter of 60 mm is the key technology component of the high‐resolution multiple‐species atmospheric profiler in the NIR (HiMAP‐NIR), which is a spaceborne instrument concept crafted to be a core payload of NASA's new generation Earth System Observatory. HiMAP‐NIR will enable the aerosol profiling in Earth's planetary boundary layer (from surface to2 km altitude) by simultaneously measuring four spatial‐spectral‐polarimetric images from 680 to 780 nm. Through detailed optimization of hybridized resonant modes in IRUs, the PBS metagrating shows a diffraction efficiency of 70% (or better) for all four linear‐polarized incident light, and polarization contrasts between orthogonal states are 0.996 (or better) from 680 to 780 nm. It meets the stringent performance required by the HiMAP‐NIR exploiting a new paradigm for the broad applications of metasurfaces. Abstract : An polarized beam splitter, enabling to simultaneously measure four spatial‐spectral‐polarimetric images with an efficiency ≈70% in the entire near‐infrared oxygen bands and a polarization contrast greater than 0.996, are realized by hybridized gap‐plasmonic metasurfaces. This meets the standard of NASA's high‐resolution multiple‐species atmospheric profiler instrument for aerosol profiling in the planetary boundary layer.